Layer-Specific Intracolumnar and Transcolumnar Functional Connectivity of Layer V Pyramidal Cells in Rat Barrel Cortex - Dirk Schubert; Jochen F. Staiger; Nichole Cho; Rolf Kötter; Karl Zilles; Heiko J. Luhmann (2001)
Layer V pyramidal cells in rat barrel cortex are considered to play an important role in intracolumnar and transcolumnar signal processing. However, the precise circuitry mediating this processing is still incompletely understood. Here we obtained detailed maps of excitatory and inhibitory synaptic inputs onto the two major layer V pyramidal cell subtypes, intrinsically burst spiking (IB) and regular spiking (RS) cells, using a combination of caged glutamate photolysis, whole-cell patch-clamp recording, and three-dimensional reconstruction of biocytin-labeled cells. To excite presynaptic neurons with laminar specificity, the release of caged glutamate was calibrated and restricted to small areas of 50 × 50 μm in all cortical layers and in at least two neighboring barrel-related columns. IB cells received intracolumnar excitatory input from all layers, with the largest EPSP amplitudes originating from neurons in layers IV and VI. Prominent transcolumnar excitatory inputs were provided by presynaptic neurons also located in layers IV, V, and VI of neighboring columns. Inhibitory inputs were rare. In contrast, RS cells received distinct intracolumnar inhibitory inputs, especially from layers II/III and V. Intracolumnar excitatory inputs to RS cells were prominent from layers II–V, but relatively weak from layer VI. Conspicuous transcolumnar excitatory inputs could be evoked solely in layers IV and V. Our results show that layer V pyramidal cells are synaptically driven by presynaptic neurons located in every layer of the barrel cortex. RS cells seem to be preferentially involved in intracolumnar signal processing, whereas IB cells effectively integrate excitatory inputs across several columns.